An evidence-based approach to critical incident scenario development. Issue 3 (11th November 2020) - Jenkins, Bryce; Semple, Tori; Bennell, Craig
Abstract : Purpose: There has been an increasing emphasis on developing officers who can effectively make decisions in dynamic and stressful environments to manage volatile situations. The aim of this paper is to guide those seeking to optimize the limited resources dedicated to police training. Design/methodology/approach: Drawing on research related to stress exposure training, principles of adult learning, the event-based approach to training and policing more broadly, the authors show how carefully crafted training scenarios can maximize the benefits of police training. Findings: The authors' review highlights various training principles that, if relied on, can result in scenarios that are likely to result in the development of flexible, sound decision-making skills when operating under stressful conditions. The paper concludes with an example of scenario development, which takes the reviewed principles into account. Originality/value: The authors hope this discussion will be useful for police instructors and curriculum designers in making evidence-informed decisions when designing training scenarios.